Restoration of Morphine-Induced Amnesia by Pediococcus acidilactici, an Indigenous Probiotics of Iran, in Male Wistar Rats - mohammadi, minoo (Archives of Medical Laboratory Sciences, 2019)
Background: Probiotics are living microorganisms that have beneficial effects on the microbial balance of the host intestine (human and animal). Studies demonstrated that intestinal microbiota maybe affect the hormones of brain and nervous through the vagus nerve. The goal of this study was to investigate the impact of Lactobacillus Pediococcus acidilactici, indigenous probiotics of Iran isolated from traditional dairy products, on passive avoidance learning of male Wistar rats. Material and Methods: In this research, 80 male Wistar rats weighing from 80 to 100 grams were used. For induction of amnesia, morphine was used as an intraperitoneal injection. Afterward, the mice were with 0.1 ml of milk alone or containing 109 CFU/ml of. Pediococcus acidilactici for 8 months. In this study, a non-active avoidance learning behavioral test was used to test long-term memory in Wistar rats. Results: Results displayed that in the control group, morphine (1 mg/rat) significantly decreased learning. In the groups receiving probiotic and probiotic extract plus morphine, there was a significant difference in learning circumstances with the control group. Conclusions: The results of this study depict the beneficial effect of Pediococcus acidilactici, a native Iranian probiotic isolated from dairy products, in the learning quality of non-active conditional avoidance in rats induced by morphine. This indicates the effect of oral probiotics on improving memory and learning.